2015
DOI: 10.1016/j.jcis.2015.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of new ion-selective cross-linked poly(vinylimidazole-co-ethylene glycol dimethacrylate) using a double-imprinting process for the preconcentration of Pb2+ ions

Abstract: A new ion-selective cross-linked poly(vinylimidazole-co-ethylene glycol dimethacrylate) prepared via a double-imprinting process was developed for the recognition and preconcentration of Pb(2+) from water samples. The sorbent was characterized by FT-IR, SEM, TGA and textural data. The maximum dynamic sorption capacity of Pb(2+) was 42.04 mg Pb(2+) g(-1) of the double-imprinted polymer. The sorption kinetics data were described by a pseudo-second-order model. The double-imprinted polymer exhibited a higher sorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…The lower surface area of the nanocomposite resulted from the low pore volume, which can be explained by the penetration of MWCNTs into the polyvinylpyridine network to occupy the pores of the polymer. On the other hand, the textural data of polyvinylpyridine are similar to those of other polymers synthesized by bulk methods, 39 and the particles have irregular shapes with rough surfaces.…”
supporting
confidence: 57%
“…The lower surface area of the nanocomposite resulted from the low pore volume, which can be explained by the penetration of MWCNTs into the polyvinylpyridine network to occupy the pores of the polymer. On the other hand, the textural data of polyvinylpyridine are similar to those of other polymers synthesized by bulk methods, 39 and the particles have irregular shapes with rough surfaces.…”
supporting
confidence: 57%
“…This parameter was determined as the ratio between the slopes calculated for the Cd 2+ preconcentration using 3-MPTMS-grafted CB and the Cd 2+ direct aspiration into the FAAS (without preconcentration). 46 The LOD and limit of quantification (LOQ), calculated according to the International Union of Pure and Applied Chemistry (IUPAC) reccomendation as three and ten times the standard deviation for the blank solution (n = 10) were found to be 0.20 and 0.66 µg L −1 , respectively. 47 The values of concentration efficiency (CE), consumptive index (CI) and sample throughput were determined as described in the literature and were found to be 7.35 min −1 , 0.54 mL and 12 h −1 , respectively.…”
Section: Interference Studiesmentioning
confidence: 98%
“…The peaks at 1,151 and 1,251 cm −1 and the peak with high intensity at 1,726 cm −1 can be referred to the C−O stretching and the C=O vibration of the ester group of EGDMA, respectively. The C=O vibration of the ester group of EGDMA was noted at 1,720, 1,738 and 1,721 cm −1 by Kara et al in 2004 [32], Segatelli et al in 2010 [36], and Tarley et al in 2015 [37], respectively. The characteristic peaks of imidazole ring in the polymer microspheres appear at 1643 cm −1 (stretching of C=C and C=N), 1,458cm −1 (stretching of C−C and C−N), 1,390 cm −1 (the C−N stretching modes for the ring), and 954 cm −1 (in-plane ring C−H bending) [32].…”
Section: Characterization Of the [Poly(egdma-vim)] Microspheresmentioning
confidence: 93%
“…In our previous studies, we reported the adsorption capacity of the poly(ethylene glycol dimethacrylate-n-vinyl imidazole) [poly(EGDMA-VIM)] beads for Cr(VI) [31], Hg(II), Cd(II), and Cu(II) [32] as well as its immobilization of tyrosinase [33], yeast invertase [34], and α-amylase [35] on Cu 2+ chelated [poly(EGDMA-VIM)] beads. Additionally, the poly(ethylene glycol dimethacrylate-co-vinylimidazole) was used for removal of Cd 2+ [36], and Pb 2+ [37] as well as the solid phase extraction of selected non-steroidal anti-inflammatory drugs [38] and purification and isolation of phenolic acids [39]. Furthermore, PEGMA-VI microspheres were used as an adsorbent for removal of Cu(II) [40], Cr(VI), and Ni(II) [41].…”
Section: İ öZdemir Et Al / Desalination and Water Treatment 159 (20mentioning
confidence: 99%